GNA15 predicts poor outcomes as a novel biomarker related to M2 macrophage infiltration in ovarian cancer - Liu, Qin; Sun, Yabing; Zhang, Tao; Lin, Wanrun; Zhang, Jing; Zhang, Huijuan; Zheng, Wenxin; Xu, Hong; Zhou, Feng (Frontiers in Immunology, 2025)
BackgroundThe exploration of genetic signatures within the ovarian cancer (OC) tumor microenvironment (TME) remains limited. M2-like tumor-associated macrophages (M2-like TAMs) are pivotal in OC progression and therapy. This study aims to establish a novel prognostic signature and identify M2-like TAM-related biomarkers in OC using RNAseq-based transcriptome analysis.MethodsPrognostic M2-like TAM-related genes were identified through univariate Cox regression, consensus clustering, and LASSO regression. Immune landscape analysis was conducted to assess immune cell composition and immune checkpoint genes in high- and low-risk groups. Subsequently, in vitro cell experiments and OC cohorts were performed.ResultsGene set enrichment analysis revealed that GNA15 is involved in immune responses like leukocyte transendothelial migration and FcγR-mediated phagocytosis. GNA15 was up-regulated in cisplatin-resistant OC cells, and its in vitro down-regulation decreased cell proliferation. An eight-gene prognostic model, including M2-like TAM-related genes, independently predicted poor outcomes in OC. GNA15 emerged as a hub gene positively correlated with M2-like TAMs infiltration, predicting unfavorable outcomes across OC cohorts. Moreover, GNA15 expression correlated positively with CD163 expression, suggesting its role in macrophage polarization.ConclusionGNA15 plays an immunosuppressive role in OC progression linked to M2-like TAMs polarization and stands as a potential prognostic marker in OC.